VISUAL OUTCOME AFTER INTRAVITREAL BEVACIZUMAB (AVASTIN) IN THE TREATMENT OF BRANCH RETINAL VEIN OCCLUSION - Naeem, Saquib; Rafe, Abdul (Pakistan Armed Forces Medical Journal, 2019)
Objective: To evaluate the visual outcome after intravitreal injection of bevacizumab (Avastin) in patients with branch retinal vein occlusion.Study Design: Prospective study.Place and Duration of Study: Combined Military Hospital (CMH) Kharian, from Mar 2016 to Nov 2017.Material and Methods: Patients of branch retinal vein occlusion (BRVO), were injected with minimum of one intravitreal bevacizumab 1.25 mg in 0.05 ml. Patients were examined using Snellen visual acuity testing, Fundus Fluorescein Angiography (FFA) and Optical Coherence Tomogragphy (OCT). Detailed eye examination was done before the procedure and follow-up visit on monthly basis was done for six months.Results: Twenty eight eyes of 28 patients were included, with a mean age of 63 years (SD 16.1). The patients received a mean of 3 (SD 1.30) injections of bevacizumab per eye. No adverse events were seen. At the baseline the mean central macular thickness was 559 microns which improved to 380 micron at 3rd month (p